Analysis of Clinical Negligence Claims Arising from Thyroidectomy in the UK from 1995 to 2013. (2nd September 2014) - Mathew, Rajeev; Tornari, Chrysostomos; Hay, Ashley; Odutoye, Babtunde
Abstract : Objectives: Determine the outcome and cause of negligence claims relating to thyroid surgery in the National Health Service (NHS). Methods: A request was submitted to the NHS Litigation Authority for claims relating to thyroid surgery between 1995 and 2013 by searching for the key words: "thyroid, " "endocrine, " or "neck." Claims were analyzed for cause of injury, type of injury, outcome of claim, and costs. Results: Of 132 cases, 90% were closed with 55% of closed claims leading to payment of damages and 72% of closed claims leading to payment of any sort (including settlement out of court). Fifty‐two percent of claims were related to complications of surgery with the rest being related to errors in diagnosis and treatment. Lack of informed consent was claimed in 11 cases. The most common injuries claimed were vocal cord dysfunction (n = 28) followed by endocrine disturbance such as hypocalcemia or hypothyroidism (n = 20). Eight fatalities occurred, of which 7 were due to hematoma and one was due to hypocalcemia. The highest payment was £945, 700 ($1, 585, 000) for bilateral vocal cord paresis requiring a permanent tracheostomy. The median payment per claim was £21, 390 ($35, 850). Conclusions: Thyroidectomy‐related claims in the National Health Service are rare but have a high success rate. Negligence from operator error correlates well with known complications of thyroid surgery. However, a significant proportion of claims are not related to surgery and represent areas where good care should be addressed by a multidisciplinary approach to the management of thyroid pathology.